Markov Model for HF Spectrum Occupancy - Balint, Cornel; De Sabata, Aldo (2019 International Symposium on Signals, Circuits and Systems (ISSCS), 2019)
Measurement of spectrum occupancy in different frequency bands and spectrum occupancy data modeling are subject of increased attention given that the whole radio spectrum becomes more and more busy. In this paper a Markov chain model for time domain spectrum occupancy is presented. The model is validated using real data measurements of the spectral occupancy in the Western part of Romania in some high frequency (HF) bands. Signals have been acquired using Universal Software Radio Peripheral (USRP) equipment and a broadband antenna and spectrum occupancy values have been calculated off-line for a set of frequency bands that present interest for establishing of a system for emergency communications in HF band. The existence of the Markov model is proved, and the accuracy of the model is presented. The results show that Markov chains can accurate model the statistical properties of spectrum occupancy in HF domain.